Chondrocyte Heterogeneity; It Is the Time to Update the Understanding of Cartilage Histology - Yasser A. Ahmed (South Valley University, 2018)
Chondrocytes were described as one cell populations in most cartilage literature.Two different chondrocyte populations; dark and light, were described in the articular cartilage and a third population, adipochondrocytes, was described in the elastic cartilage. The current literature of cartilage histology should be updated and highlight that three different populations of chondrocytes are existed in cartilage.